Population-based survey of the prevalence and types of glaucoma in Bangladesh - Bipul Kumer De Sarker; Sheikh M A Mannaf; Siddiqur Rahman; Md Shafiqul Islam; Md Mizanur Rahman; M Nazrul Islam; Salma Parvin (BMJ Open Ophthalmology)
Background To delineate the epidemiological landscape of glaucoma using a population-based sample representative of Bangladesh.Methods Using multistage stratified cluster random sampling, households were selected to identify individuals ≥35 years across all 8 divisions of Bangladesh. Sampling frames were derived from the 2011 national census. Fifty-eight study examination sites were set up for comprehensive eye evaluations, including intraocular pressure, gonioscopy and visual field testing when indicated. International Society for Geographic and Epidemiological Ophthalmology definitions were used to define glaucoma and glaucoma suspect cases.Results One hundred forty clusters (89 rural and 51 urban) were randomly selected, and 13 791 residential households were visited. We invited 17 002 individuals ≥35 years for on-site examination, of which 12 000 (71%) complied, with a male-to-female ratio of 1:1. The prevalence of glaucoma was 3.2% (95% CI 2.79% to 3.64%), and glaucoma suspect was 10.1% (95% CI 9.05% to 11.12%). The majority (78%) had primary open-angle glaucoma (POAG), while angle closure was seen in 16%. Of the POAG, 83% (n=251) were normal-tension glaucoma. Multivariable logistic regression showed increasing age (OR=1.01 for every 5-year increment, 95% CI 1 to 1.01) and male gender (OR=1.43, 95% CI 1.15 to 1.77) to be associated with an increased risk of glaucoma.Conclusions The prevalence of glaucoma in Bangladesh is 3.2% in ≥35-year-old individuals with older men most at risk. Extrapolating the results, we estimate about 2 million patients with glaucoma. Though normal-tension variety was the most common type, caution should be exercised in generalising these results to other populations.